2019
DOI: 10.3389/fmars.2019.00556
|View full text |Cite
|
Sign up to set email alerts
|

Advancing Coastal Risk Reduction Science and Implementation by Accounting for Climate, Ecosystems, and People

Abstract: Climate change and population growth are degrading coastal ecosystems and increasing risks to communities and infrastructure. Reliance on seawalls and other types of hardened shorelines is unsustainable in an era of rising seas, given the costs to build and maintain these structures and their unintended consequences on ecosystems. This is especially true for communities that depend on coastal and marine ecosystems for livelihoods and sustenance. Protecting and restoring coral reefs and coastal forests can be l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(65 citation statements)
references
References 68 publications
(117 reference statements)
0
41
0
Order By: Relevance
“…While coral reef-based activities such as snorkeling and diving are comparatively less preferred by tourists, the reefs remain a substantial draw and provide many ecosystem services such as storm protection and fisheries’ habitat. Silver et al (2019) modeled the coastal protection benefits of ecosystems in the Bahamas and found that these ecosystems were vital in reducing shoreline exposure to coastal hazards for all Bahamian islands. This was also evident in our study where the northern side of the NP Island, where the majority of the tourism infrastructure located, benefits from wave attenuation and storm protection provided by the nearby Cays and the fringing reef.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While coral reef-based activities such as snorkeling and diving are comparatively less preferred by tourists, the reefs remain a substantial draw and provide many ecosystem services such as storm protection and fisheries’ habitat. Silver et al (2019) modeled the coastal protection benefits of ecosystems in the Bahamas and found that these ecosystems were vital in reducing shoreline exposure to coastal hazards for all Bahamian islands. This was also evident in our study where the northern side of the NP Island, where the majority of the tourism infrastructure located, benefits from wave attenuation and storm protection provided by the nearby Cays and the fringing reef.…”
Section: Discussionmentioning
confidence: 99%
“…The country is aiming to develop tourism on family islands and new destinations through strengthening their intra-island airlift and transportation linkages to increase visitation beyond the NP/PI islands ( National Development Plan, 2017 ). Some islands such as San Salvador, Great and Little Inagua, Mayaguana and the Ragged Island Chains have less exposed shorelines due to their higher elevations, rocky shorelines and lower exposure to storm surge as compared to the more vulnerable Abaco, Andros and NP/PI islands ( Silver et al, 2019 ). The potential of extending tourism to these islands needs to be explored to effectively manage the growing industry.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This must reach beyond ocean acidification, as extreme ocean events including harmful algal blooms, hypoxia, and marine heat waves have recently tested management systems and stressed marine-dependent socioeconomic systems (223). Emphasizing disaster risk reduction (224) and rigorously incorporating uncertainty (225) in marine policy and governance can greatly improve outcomes for both social and ecological systems affected by ocean change (226).…”
Section: Interventions and Adaptationsmentioning
confidence: 99%